Investigation of combustion characteristics of critical quenching hydrogen mixing ratios in the presence of ordered porous media - Yunlong Zou; Ganbo Deng; Yulong Duan (Scientific Reports)
Abstract In order to promote low-carbon sustainable development in the ecological environment and improve the efficiency of hydrogen and natural gas energy utilization, this project carried out research on the explosive effects of different thicknesses of ordered porous media on the hydrogen-methane gas mixture. A detailed discussion was conducted based on the critical quenching hydrogen blending ratio under the thicknesses of 50 mm and 60 mm of ordered porous media. The results indicate that the critical quenching hydrogen blending ratio is 9% for a thickness of 50 mm and 20% for a thickness of 60 mm, indicating that greater thickness enhances flame suppression capabilities. Between the critical quenching hydrogen blending ratio range for thicknesses of both 50 mm and 60 mm, the peak values of flame front velocity, reverse diffusion flame length, and explosion pressure initially decrease and then subsequently increase with an increasing hydrogen content. As the thickness of the flame retardant medium augments, there is an increase in both the flame velocity and the reverse diffusion length at the critical hydrogen concentration. However, the pressure peak observed at a thickness of 50 mm surpasses that at 60 mm. The pressure curve experiences sudden fluctuations due to the combined effects of explosion pressure and heat transfer, with the initial point of this abrupt change closely linked to the thickness of the ordered porous media. Therefore, it is imperative to maintain hydrogen content below the critical quenching hydrogen blending ratio to ensure the safe transport and utilization of hydrogen and natural gas energy.